The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1001/archsurg.134.10.1041
|View full text |Cite
|
Sign up to set email alerts
|

Six Years of Surgical Wound Infection Surveillance at a Tertiary Care Center

Abstract: Hypotheses: (1) Antibiotic restriction policies result in alteration of microbiologic features of surgical site infections (SSIs) and (2) reported SSI rates are underestimated when postdischarge surveillance is not included in SSI surveillance efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(32 citation statements)
references
References 39 publications
1
27
2
2
Order By: Relevance
“…This is likely related to bacterial proliferation evoking an immune response and altering normal collagen synthesis and wound healing. With underlying organ dysfunction and immunosuppressive medications, transplant patients are at increased risk for SSI [28] and, subsequently, incisional hernias. Thus efforts to 1) recognize and aggressively treat SSI and 2) reduce infections would likely have secondary benefits of reducing the risk of hernia formation.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely related to bacterial proliferation evoking an immune response and altering normal collagen synthesis and wound healing. With underlying organ dysfunction and immunosuppressive medications, transplant patients are at increased risk for SSI [28] and, subsequently, incisional hernias. Thus efforts to 1) recognize and aggressively treat SSI and 2) reduce infections would likely have secondary benefits of reducing the risk of hernia formation.…”
Section: Discussionmentioning
confidence: 99%
“…whether cellulitis cases are included or excluded), 20 and differences in surveillance methods to ascertain SSI cases. 9, 21 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one published study found an inpatient SSI rate of 0.4% and an outpatient SSI rate of 2.4% within 30 days after breast surgeries. 18 Another found that the rate of SSI after breast biopsy doubled when a post-discharge surveillance program was instituted. 19 …”
Section: Discussionmentioning
confidence: 99%